Nine Mn(II), Zn(II) and Cd(II) mixed-ligand coordination networks with rigid dicarboxylate and pyridine-n-aldoxime ligands: Impact of the second ligand in the structures' dimensionality and solvent capacity. (17th June 2017) - Croitor, Lilia; Coropceanu, Eduard B.; Duca, Gheorghe; Siminel, Anatolii V.; Fonari, Marina S.
Graphical abstract: Nine coordination polymers based on Mn(II), Zn(II) and Cd(II) ions were synthesized using fumaric, 1, 3-benzenedicarboxylic and 1, 4-benzenedicarboxylic acids as bridging ligands and two isomeric pyridine-n-aldoximes ( n = 2, 4) as terminal ligands. All the compounds were tested as luminescent materials and the Cd-based polymers reveal the highest emission response. Abstract: Using the 'dicarboxylic acid/oxime blend approach' nine coordination polymers, [M(fum)(2-pyao)2 ] n, M = Mn(II), Zn(II), Cd(II) (1 –3 ), [Mn(1, 3-bdc)(2-pyao)2 ] n (4 ), [Cd(1, 3-bdc)(2-pyao)] n (5 ), [Cd(1, 3-bdc)(4-pyao)(H2 O)2 ]·dmf·H2 O n (6 ), [Cd(1, 4-bdc)(4-pyao)2 (H2 O)]·dmf n (7 ) and [M(1, 4-bdc)(4-pyao)2 ]·dmf n, M = Zn(II), Cd(II) (8, 9 ) (where 2-pyao = pyridine-2-aldoxime, 4-pyao = pyridine-4-aldoxime, fumH2 = fumaric acid, 1, 3-bdcH2 = 1, 3-benzenedicarboxylic acid and 1, 4-bdcH2 = 1, 4-benzenedicarboxylic acid) have been prepared, and their crystal structures have been determined by single crystal X-ray diffraction. Compounds1 –4, 6 and7 represent 1D coordination polymers, while compounds5, 8 and9 represent laminar 2D structures. In compounds1 –4 two terminal 2-pyao ligands take the common bidentate chelating coordination mode that results in five-membered chelate rings revealing a "butterfly wings" shape. The oxime's hydroxyl group participates in an intramolecular OH⋯O hydrogen bond with the dicarboxylic oxygen atoms, which are uncoordinated to the metal center, thus fortifying the metals' coordination cores. In6 –9 the pillared monodentate 4-pyao ligands, due to their bulkiness and terminal hydroxyl-groups, essentially increase the solvent accessible areas, and the hydrophilic regions in the structures facilitate the accommodation of polar solvents (dmf and water) and their retention in the crystal lattice via hydrogen bonding with OH-ligands (4-pyao, water). All the compounds were tested as luminescent materials, with the Cd-based polymers3, 5 and6 revealing the highest emission response.